Differences In The Competencies Of Certified And Non-Certified Physical Education, Sports And Health Teachers In State Vocational High School - Ade Sunandar; Akhmad Sobarna; Muchamad Ishak (UNIB Press, 2025)
The purpose of this study was to determine the differences in the competency of certified and non-certified physical education teachers at Public vocational high school Tangerang Regency. The method used in this study was a survey. The population of principals and vice principals at Public vocational high school Tangerang Regency, the sampling technique used the Purposive Sample technique, the sample was taken from only 12 schools that had certified and non-certified physical education teachers. The questionnaire instrument. Based on data obtained from respondents, 12 principals can be seen that the majority of principals at Public vocational high school Tangerang Regency, namely 100%, assessed that certified physical education teachers have high competencies, while 100% assessed that non-certified physical education teachers have moderate competencies. Meanwhile, according to the assessment of the Vice Principal of 12 respondents, it was said that the majority of Certified Physical Education Teachers, namely 83%, have high competencies and 17% have moderate competencies and the Competence of Non-Certified Physical Education Teachers, namely 75% have moderate competencies and 25% have low competencies.